“You can’t really have a relationship with them because they just ask you questions”: understanding adolescent dropout – an empirical single case study - Cirasola, Antonella; Szegedi, Dora; Fonagy, Peter; Midgley, Nick (Frontiers in Psychology, 2024)
High dropout rates are common in youth psychotherapy, including psychoanalytic psychotherapy, yet the reasons behind this trend remain obscure. A critical focus to enhance adolescent engagement could be the therapeutic alliance, particularly in resolving alliance ruptures. This study sought to clarify the complex relationships between the therapeutic alliance, encompassing alliance ruptures and resolutions, and dropout within the context of poor outcome. It investigates a single case of an adolescent with depression who dropped-out of Short-Term Psychoanalytic Psychotherapy, without showing clinical improvement. Data was garnered from diverse sources, including questionnaires, interviews, and session recordings, and analyzed through a mixed-method longitudinal framework. This encompassed views from the adolescent, therapist, parents, and external evaluators. The study identifies several factors impacting the decision to drop out, including initial profound distrust towards the therapist, a complex and difficult therapeutic relationship characterized by unresolved alliance ruptures, and sporadic attendance. External factors including minimal parental engagement with therapy were also seen as detrimental to the adolescent's involvement and progress. The research underscores the challenges in engaging adolescents, especially when there may be distrust of professionals, and in the absence of parental involvement with treatment.